Formative assessment in higher education: a case study - doi: 10.4025/actascihumansoc.v33i1.9214 - Ribeiro, Luis Roberto de Camargo (2011)
This study, of a qualitative nature, discusses an implementation of Problem-based Learning (PBL) and, in particular, its assessment system from the students’ standpoint in the context of a course at a public university in Brazil. PBL is a teaching-learning approach that uses problems to initiate, focus, and motivate the acquisition of professionally (and socially) desired concepts, skills and attitudes. Besides written essay tests, required by the institution, the assessment system adopted by the teacher in charge of the course comprised peer assessment, self-assessment, and assessment of the instructional process. The research data, collected by means of participant observation and an end-of-term questionnaire, point to student satisfaction regarding the adopted assessment system and indicate some dysfunctions (e.g., increased time consumption and occurrence of ‘free rides’). Yet, according to the students, the adopted system promotes teamwork and is consistent with PBL’s theoretical underpinnings and principles.